El barrio alfarero de Cartuja (Granada, España). Análisis de un testar localizado en las recientes intervenciones del Sector Beiro - Bustamante-Álvarez, Macarena; Sánchez López, Elena H. (Rei Cretariae Romanae Fautorum Acta, 2022)
The recent archeological excavations carried out at the potter’s workshops in Cartuja are included within the activities developed within a Master Degree of Archeology of the University of Granada and covered by the General Project of Research Campus de Cartuja. This paper serves to present a stratigraphic study of typological character of the productions of this emblematic workshop of the Eastern Baetica. Specifically, we analyze a ceramic discard with huge number of pieces that we associate with one of the largest furnaces of this ceramic complex. Among the pieces found are waste of common ceramics, red slip ware and terra sigillata. Also there are some potter instruments that allow us to analyze their productive mode.